THE EFFECT OF PARENTING STYLES ON THE DEVELOPMENT OF A SENSE OF RESPONSIBILITY IN PRESCHOOL CHILDREN - Laisha Zahra; Asep Kurnia Jayadinata; Nurdiansyah Nurdiansyah (LP2M IAI Al-Khairat Pamekasan, 2026)
The development of responsibility character in early childhood is a crucial aspect that cannot be separated from the role of parents in the parenting process. This study aims to describe the influence of parenting styles on the formation of responsibility character in early childhood within the community of Cikampek Barat Village, RW 18, Karawang Regency. This study employed a descriptive qualitative approach with data collection techniques consisting of observation and open-ended interviews. The research subjects comprised five early childhood children aged 4–6 years and five parents as the primary informants. Data validity was examined through triangulation techniques, while data analysis was conducted using the interactive analysis model of Miles and Huberman, encompassing three stages: data reduction, data presentation, and conclusion drawing. The results indicate that the parenting styles applied by parents are not singular in nature but vary in accordance with family habits and communication patterns. Two dominant parenting styles were identified, namely democratic parenting and authoritarian parenting. Children raised under democratic parenting demonstrated more optimal development of responsibility character, characterized by greater independence, openness, and self-awareness. In contrast, children raised under authoritarian parenting tended to exhibit compliance driven by fear rather than by an internalized understanding of responsibility values. This study affirms that an appropriate parenting style, one that integrates warmth, effective communication, and reasonable supervision, is proven to support the formation of stable responsibility character in early childhood.